MOTIVASI REMAJA DALAM MELAKUKAN DONOR DARAH PADA MASA PANDEMI COVID-19 DI DEPOK JAWA BARAT - Cita Reast Wulansari; Alfi Kurnia Septiane (Ensiklopedia of Journal, 2022)
Blood donation is a person's voluntary activity to save human lives. A person's willingness to donate blood is supported by the motivation (encouragement) that exists in the donor. The Covid-19 pandemic is a challenge for all human beings in the world to carry out humanitarian activities, the existence of donors has an important role in helping those who always need blood transfusions. Adolescents have the potential to donate blood because this is a time when they have a high sense of humanity. This study aims to determine the motivational factors that influence adolescents in donating blood during the Covid-19 pandemic. This Method is qualitative fenomenological research with triangulation method. The research was conducted at UDD PMI Depok city by interviewing 10 donors Adolescents aged 18-21 years. The results of this study indicate that intrinsic and extrinsic motivation influence adolescents in donating bloodKeyword : Adolescent, blood donation, Motivation